2003
DOI: 10.1034/j.1600-0714.2003.00086.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical detection of matrix metalloproteinases (MMPs) and tissue inhibitors of metalloproteinases (TIMPs) in ameloblastomas

Abstract: Expression of MMPs and TIMPs was considered to be associated with interactions between epithelial cells and mesenchymal components in normal and neoplastic odontogenic tissues; these molecules might play a role in regulation of tumor progression in ameloblastomas as well as regulation of developmental processes in tooth germs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

16
77
0
14

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(107 citation statements)
references
References 27 publications
16
77
0
14
Order By: Relevance
“…Similarly to the present study, Silveira et al 8 observed more pronounced expression of MMP-9 in the mesenchymal component of KOTs compared with RCs and DCs, a finding supporting the hypothesis of a more aggressive behavior of this tumor compared with other cysts. In the study by Kumamoto et al, 15 immunoreactivity to MMP-9 was stronger in the stroma of ameloblastomas than in the mesenchymal component of tooth germs, suggesting that an increased production of this protein by neoplastic cells is related to the transformation of odontogenic tissues and aggressiveness of this tumor. Ribeiro et al 29 also found intense immunostaining for this gelatinase in the parenchyma and stroma of ameloblastomas, indicating its possible participation in the growth of these tumors.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Similarly to the present study, Silveira et al 8 observed more pronounced expression of MMP-9 in the mesenchymal component of KOTs compared with RCs and DCs, a finding supporting the hypothesis of a more aggressive behavior of this tumor compared with other cysts. In the study by Kumamoto et al, 15 immunoreactivity to MMP-9 was stronger in the stroma of ameloblastomas than in the mesenchymal component of tooth germs, suggesting that an increased production of this protein by neoplastic cells is related to the transformation of odontogenic tissues and aggressiveness of this tumor. Ribeiro et al 29 also found intense immunostaining for this gelatinase in the parenchyma and stroma of ameloblastomas, indicating its possible participation in the growth of these tumors.…”
Section: Discussionmentioning
confidence: 89%
“…6 Several factors have been associated with the aggressive behavior of ameloblastomas, such as an increased proliferation potential, 12 alterations in the expression of tumor suppressor genes, and the aberrant expression of cell cycle-regulating proteins, 13 adhesion molecules, 14 and MMPs and their inhibitors (TIMPs). 15 In addition, Silveira et al 8 suggested that the mechanism of expansion of KOTs, DCs, and RCs may also be influenced, or even be conducted, by the secretion of MMPs. Thus, an exuberant expression of MMPs might be related to a higher aggressiveness of cystic lesions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[13][14][15] MMP-1 (collagenase-1, interstitial collagenase), synthesized by a wide variety of normal cells, such as fibroblasts, macrophages, and endothelial and epithelial cells, is one of the major proteases that can degrade the triple-helical domain of type I fibrillar collagen. [16][17][18] Type I collagen, responsible for connective tissue strength and rigidity, is the main component of the organic bone matrix. 19 A possible role for MMP-1 in keratinocyte migration 18 has been reported and the overexpression of this protease can be observed in advanced epithelial malignant tumors.…”
mentioning
confidence: 99%